Rationale for Defining Recognition of “Higher Animal Welfare” Farm Assurance Schemes in a Global Food System: The GAWA Alliance - Rowe, Elizabeth; Rix, Jeremy; Mullan, Siobhan (Frontiers in Animal Science, 2021)
Many schemes exist which provide assurance on farm animal welfare. However, different standards and protocols mean the level of welfare assured by schemes can be very diverse, potentially hindering food businesses operating globally from sourcing equivalent higher welfare products. This research investigated the rationale for establishing a recognised network of higher welfare schemes from which authentic higher welfare products can be purchased. Nine assurance schemes and seven food businesses were interviewed. Results confirmed the challenge food businesses face in international trade of products from animals reared to a definable welfare status, due to the lack of recognised equivalence of different assurance schemes. Results provided evidence for international interest in an alliance of higher welfare schemes to provide standardisation of higher welfare, as a solution to this challenge. As a result, a working model of such an alliance was refined and the alliance was launched as “Global Animal Welfare Assurance” (GAWA).